Optimizing access to fruits and vegetables in rural communities: A decision-making model for the placement of produce markets - Eduardo Pérez; Cassandra M. Johnson; Yan Li; José A. Pagán (PLoS ONE, 2025)
Many rural communities experience limited access to fruits and vegetables (FV) and may benefit from food environment interventions to increase the number of produce markets selling FV. Systems analysis is an innovative approach for informing policy, systems, and environmental (PSE) change interventions for the food retail environment. However, there has been little research. This study describes a new decision-making model that optimizes placement of new FV markets in a rural community in Texas based on combinations of three intervention factors: recommended driving distance to nearest produce market, service capacity of new and existing FV markets, and financial resources. Models estimated the potential effects of three intervention outcomes: the number of new FV markets, the ratio of fast food outlets to FV markets, and population coverage. Secondary sources of data were used in the models. The analysis tested 27 different interventions and compared effects to a benchmark. The smallest increase in population coverage or the local population’s access to FV was 19% compared to benchmark, while other interventions increased access to 100%. Models showed that the largest relative gain in access to FV, 29% to 37% for the local population, was at a lower level of financial resource availability ($1516171819-20,000). Findings provide evidence for the potential effects of food environment changes for one rural Texas community. Stakeholders can generate insights to inform context-specific decisions about their communities. In addition, this new decision-making model can be adapted for other communities to support PSE change interventions for nutrition.